Frequency of Occurence of Phonemes in American Spanish - Guirao, Miguelina; García Jurado, María (Revue québécoise de linguistique, 1990)
AbstractA computer aided inventory of the frequency and distribution of American Spanish phonemes is reported. The corpus, drawn from five modern plays, contained 163,861 phonemes in 74,460 syllables and 43,306 words. First single elements were counted. The seven first sounds /e a o s n r i/ account for 67.5% of the total occurrences. The relative distribution of phonemes in the most frequent syllables was calculated. Higher scores correspond to /a e o/ and /s n d k t/. All phonemes were distributed according to their initial and final syllable and words position.